Motor skills related to body movement and dance. t-patterns detection - M. Castañer; C. Torrents; M. Dinušová; M. T. Anguera (Asociación Española de Ciencias del Deporte, 2010)
In the learning processes that promotes the generation of motor actions, teachers usually propose instructions based on kinetic models. The aim of this study is to observe what type of motor answers the subjects generate from kinesic models offered by the teachers. The motor answers to observe refer to the patterns of motor skills of stability, locomotion and manipulation, variations of body-space, time and interaction between participants. 12 Phsysical Activity and Sports Science students without experience in dance participated in the study. 8 sessions were observed focused on space, time, energy and body contact. A specific instrument was created, the observational system of motor skills OSMOS (Castañer, Torrents, Anguera y Dinusôva, 2008),. It was codified with ThemeCoder  (Pattern Vision, 2001) and SDIS-GSEQ   (Bakeman &  Quera, 1996) and THEME (Magnusson, 2000) were used for the reliability and detection of T-patterns . Key Words:  Motor Skills, Field Format, Body expression and dance, Motor T-Patterns detection, Kinesic's Model.